Political News In Online Media And The Development Of Hoax Narratives In The Gunung Sari Islamic Boarding School, West Lombok - Sugianto; Mohzana; Mudarman (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This article aims to analyze politics on online media and its relationship to the development of hoax narratives in Islamic boarding schools located in the Gunung Sari area, West Lombok. Through a comparison of the Islamic boarding school in Tegal and Kekait, this study examines the forms of response from the students at both Islamic boarding schools to the political news they receive. The main focus of this research is on the online media aspect and the responses of the students at the pesantren to the various hoax narratives that are spreading. This research uses a sociological approach with a qualitative method. Data was collected from structured interviews and non-participant observation. Additionally, this research used an analysis of various fake news stories circulating in online media accessed by the students as supporting data. The findings of this study are that online media contributes to the spread of hoax narratives in Islamic boarding schools in Gunung Sari. The forms of hoax narratives that spread depend on the type of online media accessed by the students.